Remote delivery of cardiac rehabilitation can achieve equivalent health-related quality of life outcomes to in-person methods in patients with coronary heart disease: a multi-site study. (29th July 2021) - Gallagher, R; Kirkness, A; Farrell, M; Roach, K; Gooley, L; Ashcroft, S; Fletcher, A; Stephenson, C; Glinatsis, H; Bruntsch, C; Roberts, J; Ladak, L; et al.
Abstract: Funding Acknowledgements: Type of funding sources: None. Background In-person exercise-based cardiac rehabilitation (CR) has well-established benefits for health-related quality of life (HRQL) for patients with coronary heart disease (CHD). During COVID-19 pandemic restrictions, remote delivery replaced in-person CR, but the impact on HRQL is unclear. This study addresses this gap. Methods Consecutive patients commencing CR at four sites in one Local Health District in Sydney were recruited (n = 194), recruited from December 2019 to October 2020. Remote delivery from March 2020 created a natural comparison group to in-person CR. HRQL was measured at CR entry and completion using the SF-12v2 and linear regression was used for analyses. Results Participants were aged mean 65.94 (SD 10.45) years, were 80.9% male and diagnoses included elective PCI (37.9%), CABG (26.7%), and MI (34.9%) either with PCI (23.6%) or alone (11.3%). Participants received remote (n = 103, 53.1%) or in-person (n = 91, 46.9%; ≥ assessment + 2 sessions) CR, with more completions for in-person (75.8% vs 63.1%, p=.03). Remote participants were more likely to be white than ethnic minority (35.2% vs 13.6% p<.001), however, there were no differences in baseline HRQL for delivery group after adjustment. HRQL improved from CR entry to completion regardless of delivery mode (adjusted). Most improvements occurred in physical function (SMD 6.37, 95% CI 4.81, 7.92), role physical (SMD 5.72, 95% CI 4.29. 7.16) and physical component (SMD 5.77 95% CI 4.43, 7.12) scores. Least improvement occurred in mental component scores (SMD 1.65, 95%CI .53, 2.78). Conclusion Remotely delivered CR provides comparable HRQL outcomes to in-person delivery, thus providing a promising alternative. Data are needed on cost-effectiveness, as well as staff and patient preferences.